2003
DOI: 10.1128/mcb.23.7.2407-2414.2003
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-Induced Activation of the Phosphatidylinositol 3-Kinase/Akt Pathway Increases Arsenite Cytotoxicity

Abstract: The inhibitory effect of caveolin on the cellular response to growth factor stimulation is well established. Given the significant overlap in signaling pathways involved in regulating cell proliferation and stress responsiveness, we hypothesized that caveolin would also affect a cell's ability to respond to environmental stress. Here we investigated the ability of caveolin-1 to modulate the cellular response to sodium arsenite and thereby alter survival of the human cell lines 293 and HeLa. Cells stably transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 44 publications
5
65
0
Order By: Relevance
“…These findings are supported by previous reports showing that caveolin 1 and 2 expression is associated with highly aggressive tumours such as inflammatory breast carcinoma (Eynden, 2005), basal-like (Savage et al, , 2008) and triple-negative breast carcinoma (Shack et al, 2003;Tan et al, 2007;Savage et al, 2007Savage et al, , 2008. Aside from breast, the association between caveolin expression and poor patient outcome was noticed in other tissue tumours (Savage et al, , 2008, including prostate (Karam et al, 2007), lung ((Ho et al, 2008), and the central nervous system (Barresi et al, 2006).…”
Section: Discussionsupporting
confidence: 77%
“…These findings are supported by previous reports showing that caveolin 1 and 2 expression is associated with highly aggressive tumours such as inflammatory breast carcinoma (Eynden, 2005), basal-like (Savage et al, , 2008) and triple-negative breast carcinoma (Shack et al, 2003;Tan et al, 2007;Savage et al, 2007Savage et al, , 2008. Aside from breast, the association between caveolin expression and poor patient outcome was noticed in other tissue tumours (Savage et al, , 2008, including prostate (Karam et al, 2007), lung ((Ho et al, 2008), and the central nervous system (Barresi et al, 2006).…”
Section: Discussionsupporting
confidence: 77%
“…The protective effect of wortmannin in our study also reflects a proapoptotic role of PI3-K. 51,52) It was reported that H 2 O 2 produced platelet-derived growth factor-b (PDGF-b) receptor tyrosine phosphorylation and downstream ATM kinase activation with profound p53 ser-15 phosphorylation involved in cell growth arrest and apoptosis, linking oxidative stress to p53 through the PDGF-b receptor and ATM. 53) In summary, the data presented here indicate that dracorhodin perchlorate induces apoptotic cell death in A375-S2 cells through accumulation of p53 and activation of caspases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PI3K is positively implicated in apoptosis induction in response to various stimuli, including hypoxia (23), arsenic compounds (24), glucose deprivation (25), and serum withdrawal (26). These findings indicate that PI3K activates two functionally opposite pathways, depending on cell type, nature of stimulus, and activities of other signaling pathways.…”
Section: Introductionmentioning
confidence: 91%